Effect of sodium acetate on stevioside production of Stevia rebaudiana - Dheeranupattana S. (2014)
Shoots of in vitro plants of Stevia rebaudiana were cultured on MS media supplemented with 16 factorial combinations of BA and NAA at the concentrations of 0, 0.5, 1 and 2 mg/L under 16 h/day fluorescent light for eight weeks. The MS medium with 1 mg/L BA was found to induce multiple shoot formation with an average of 4.5 shoots/explant. The MS medium with 2 mg/L NAA could induce root formation with the highest average number of 11 roots/explant. Analysis of natural stevioside production as well as in vitro shoots and roots using High Performance Thin Layer Chromatography indicated that the natural shoots and the in vitro roots contained 0.0188 and 0.0012 g/g dry weight of stevioside respectively. Shoots and rooted-shoots were cultured in liquid MS medium supplemented with 0, 0.1 and 0.2 mg/L sodium acetate under 16 h/day illumination for four weeks. It showed that the medium with 0.1 mg/L sodium acetate induced the highest content of stevioside in both shoot and rooted-shoot cultures at 0.0039 and 0.0054 g/g dry weight, respectively.